EKSISTENSI PESANTREN DITENGAH PUSARAN RADIKALISME DAN IDEOLOGI TRANSNASIONAL - Moh. Ainur Rokhim; Ubaidillah Wasi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2021)
Religious life in Indonesia is very dynamic with the emergence of various cases with the background of religious radicalism and transnational ideology. This phenomenon has not only developed in certain communities, but its existence has developed in a transnational global form. Islamic boarding schools as part of the Islamic tradition of the archipelago are often associated as a central understanding of fundamental Islam which is the root for the emergence of radical movements in the name of Islam. One of the efforts of religious education is to carry out a process of understanding and forming a mindset, namely by instilling the value of multiculturalism through Islamic boarding school education. This research is a library research with a conceptual and comparative approach and uses content analysis. The method used is a descriptive-analytical method. The results of this study conclude that Islam as a religion of universal compassion (rahmatan lil 'alamin) teaches education by upholding human values, respecting human rights, respecting the diversity of cultures and cultures of society, desiring peace, justice, tolerance, and attitudes that are balanced, and other manifestations of noble morals. Islamic education (pesantren) which teaches hatred of different opinions and beliefs is not ideal for the continuation of diversity and diversity in Indonesia. Islamic boarding schools infiltrated by radicalization need to be reoriented in a direction that is in accordance with the Islamic spirit which teaches mutual respect and brotherhood. A number of values ​​taught are tolerance, moderation, togetherness, equality, mutual respect and multicultural Islamic education.